The experimentally investigations on acute ivarfarine poisoned dogs and lambs and its treatment - Veysi ASLAN (Eurasian Journal of Veterinary Sciences)
This study has been madein order to fihd out the effect of Transamin (an antifibrinolitic medicine) with Vitamin K1 and to observe elinical and haematological changes on dogs and one year old lambs which experimentally poisoned by an anticoagulant rodentisit warfarin. During experimentally studies 60 dogs and 16 one year old lambs w:ere used, 50 mg/kg warfarin was given to lambs elinical symptoms, bleeding time coagulation time and protrombin time,- erythrocyte and leucocyte counts, haemoglobin contents, haematocrit values and leucocyte formula vvere determined. Experimentally poisoned dogs were grouped and following treatments were applied. a) Vitamin K1, b) Transamin, c) Vitamin K1+Transamin. The most succesfull treatment in dogs was applied to lambs. The begining of symptoms and severity was chahged with species, age and condttion of animaL During the period of increased symptom protrombin, coagulation, bleeding times and total leucocyte count were quite higher (P 0.001) than normal. In countrast, erythrocyte count, haemoglobin contents and haematocrit values were decreased (P 0.001). Changes were determined in leucocyte formula; lymphocyte 10 %, eosinophyl, 33 % decteased; neutrophyl 9.6 % increased. Treatment with Vitamin K1+Transamin combination were more succesfull in both species and webelieve this combination will be useful.